1992
DOI: 10.1002/hlca.19920750606
|View full text |Cite
|
Sign up to set email alerts
|

Di(tert‐butyl)diazomethan: Thermische Zersetzung und Einelektronen‐Redox‐Reaktionen

Abstract: Di(tevt-buty1)diazomethane: Thermal Decomposition and One-Electron Redox ReactionsDi(tert-buty1)diazomethane is a potential precursor for the still unknown, presumably sterically overcrowded tetrakis(tert-buty1)ethane and, therefore, re-investigated. Its (HeI) photoelectron spectrum exhibits a low first vertical ionization energy of only 7.45 eV. Based on the ionization pattern, both the thermal decomposition above 600 K under nearly unimolecular conditions as well as the N, elimination at the surface of conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…But carbene 5 has an alternative unimolecular reaction channel, which is kinetically favoured by both concentration and orientation effects. This is the intramolecular C-H insertion into one of the six methyl groups, to give 1,1-dimethyl-2-tert-butylcyclopropane (9). This pathway is observed experimentally and calculations give an explanation for this finding.…”
Section: Why Does Carbene 5 Not Dimerize?mentioning
confidence: 58%
See 1 more Smart Citation
“…But carbene 5 has an alternative unimolecular reaction channel, which is kinetically favoured by both concentration and orientation effects. This is the intramolecular C-H insertion into one of the six methyl groups, to give 1,1-dimethyl-2-tert-butylcyclopropane (9). This pathway is observed experimentally and calculations give an explanation for this finding.…”
Section: Why Does Carbene 5 Not Dimerize?mentioning
confidence: 58%
“…Recently Ephritikine et al found also some reduction of the keto to a methylene group, when di-tert-butylketone was treated with TiCl 4 /Li [7c]; a carbenoid species was deduced as intermediate by the authors. They have been several attempts to dimerize di-tert-butylcarbene (5), but neither low temperature photolysis of di-tert-butyldiazomethane [8], nor thermal decomposition of di-tert-butyldiazomethane yielding carbene 5 on metal surfaces any dimerization products were obtained [9]. It should be mentioned that several "tied-back" derivatives of alkene 1 such as anti-fenchylidenefenchane (6), have been successfully prepared [2, 10].…”
Section: Introductionmentioning
confidence: 99%
“…The ratio of the produced hydrocarbons 5 -7 varied with the nature of the catalyst, and chemisorbed di(tert-butyl)carbene was assumed responsible. Both radical cation and radical anion of 4 appear to lose N 2 rapidly [15]. We are not aware that reactions of 4 with Brønsted acids have been studied.…”
mentioning
confidence: 92%
“…Bock et al studied the conversions of 4 in a flow system above 600 K at 10 À2 mbar on the surface of metal catalysts [15]. The ratio of the produced hydrocarbons 5 -7 varied with the nature of the catalyst, and chemisorbed di(tert-butyl)carbene was assumed responsible.…”
mentioning
confidence: 99%
“…The structural and spectroscopic data of the heteroaromatic compounds 1 and 2, both depicted in Figure 3, which can be considered as examples of an arylated, BN-substituted ethylene, were hitherto unknown. They were prepared according to standard procedures described in Equation (1) and characterized by 1 H, 13 C, and 11 B NMR spectroscopy, UV/Vis spectroscopy, and single crystal XRD. (1) Compound 1 is a completely phenylated derivative of aminoborane H 2 B=NH 2 , which exists as a monomer only under extreme conditions [3,9,10].…”
Section: Introductionmentioning
confidence: 99%